Effects of poultry fat and choice white grease on finishing pig growth performance, general carcass characteristics, and pork longissimus muscle quality - J J Engel; J W Smith II; Robert D Goodband; John A Unruh; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1997)
Eighty-four crossbred gilts were used to exan1ine the effects of increasing dietary additions of poultry fat (PF) or choice white grease (CWG) on finishing pig growth performance, standard carcass characteristics, and longissimus muscle quality. Increasing CWG or PF improved feed efficiency. Increasing CWG tended to increase then decrease longissimus muscle visual color compared with longissimus muscles from those animals fed PF. Pigs fed CWG had firmer, less exudative, and more purplish-red (measured by a Minolta chronometer) longissimus muscles compared with pigs fed PF. Feeding CWG or PF did not affect standard carcass traits and had minimal effects on longissimus muscle quality.; Swine Day, Manhattan, KS, November 20, 1997
Keywords: Swine day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 795; Swine; Finishing pigs; Choice white grease; Poultry fat; Performance; Longissimus muscle quality